Optimalisasi Potensi UMKM Lokal: Pembuatan Kemplang Singkong untuk Meningkatkan Kreativitas dan Ekonomi Masyarakat Desa Beganding, Kabupaten Karo - Ramandha Niswan; Alifia Nasya Manurung; Tri Deby Damayanti; Mhd Habbil Frizky; Aqwa Naser Daulay (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) is a form of students’ real contribution to society, aiming to provide a positive impact on local social and economic development. The implementation of this program in Beganding Village, Karo Regency, focused on optimizing the potential of Micro, Small, and Medium Enterprises (MSMEs) through training and assistance in producing spicy cassava crackers (kemplang singkong pedas) as the village’s superior product. Beganding Village has great potential in the agricultural sector, particularly cassava production, which has not been fully utilized to improve the community’s economy. Through this activity, residents were trained to process cassava into spicy crackers using various local spices such as chili, shallots, garlic, scallions, and coriander. The processing was carried out without sun-drying but directly by frying, resulting in a distinctive taste and high market competitiveness. This study employed a qualitative descriptive method through observation, interviews, and documentation. The results show an increase in community creativity, the formation of new small business groups, and a rise in household income through the sale of cassava cracker products.